Study of the effects of honey supported by silver nanoparticles(AgNp) in the inhibition of bacteria Staphylococcus aureus and Pseudomonas aeruginosa isolated from the urinary tract infection (Journal of the College of Basic Education, 2022)
AbstractThe study were aiming to test the efficiency of nanoparticales honey and honey supported by nanoparticles inhibition of bacterial growth Staphylococcus aureus and Pseudomonas aeruginosa .Fifty isolates were obtaind with twenty five isolates of bacteria ,which caused urinary tract infection and obtained from the department of biology, collage of science, Al-Mustansiriyah University. All bacterial isolates under study showed their ability to produce the bio membrane and by 100% but to varying degrees in terms of the intensity of the composition of the membrane .And different percentages with the highest rate of inhibition at aconcentration of 4% and at a rate of (13-20)mm and the lowest rate of inhibition was based on the concentration of 1% and diameters of (4-5) mm to bacteria Staph aureus .In bacteria Ps. aeruginosa the highest rate of inhibition was at 4% concentration and diameter (8-20)mm ,while the lowest rate of inhibition at the concentration of 1% and diameter of (2-4)mm. The results showed different inhibitors with 40% concentration on bacterial Staph aureus discoloration at (12-18)mm ,while the inhibition Ps. aeruginosa rate of (10-20)mm ,and lowest inhibition was 10% (2-3)mm and bacterial. While the results showed the effectiveness of honey fortified nanoparticles in increasing the inhibition of bacterial pathology and different concentrations with the highest rate of inhibition at a concentration of 40% and the rate of inhibition diameter (22-25)mm for each bacteria Staph aureus and Ps. aeruginosa and a lower diameter of inhibition at a concentration of 10% and a rate of (2-4)mm.